Establishment and function of the rhizosphere fungal community in rare and endangered plant Alsophila spinulosa - Hui-Min, Zhang; Ling-Bin, Yan; Dong-Mei, Yuan; Feng, Liu; Xiu-Gang, Cao; Dai-Yan, Wang; Qin-Qin, He; Jun, Mu; Li-Fei, Yu; Yuan, Liu; Zhi-Fei, Chen (Frontiers in Microbiology, 2025)
IntroductionThe “rhizosphere effect” in plants occurs within approximately 5 mm from the root surface, where microbial communities exhibit distinct species composition and structural characteristics compared to non-rhizospheric soil. Root-associated fungi play crucial roles in nutrient acquisition enhancement, stress resistance improvement, organic matter decomposition, and carbon cycle promotion. Current research shows limited understanding of the rhizospheric fungal communities in Alsophila spinulosa, a rare and endangered plant species.MethodsThis study conducted a comparative analysis of fungal community composition and structural differences between A. spinulosa rhizospheric and non-rhizospheric soils. The functional roles of fungi in these distinct communities were systematically analyzed, with particular emphasis on identifying keystone fungal taxa within the rhizosphere, and explained the construction process of fungal communities.ResultsThe results showed that there was no difference in α diversity between the rhizosphere and non-rhizosphere soil fungal communities of A. spinulosa, but the β diversity was significantly differentiated, indicating that the difference between rhizosphere and non-rhizosphere fungal communities was mainly reflected in species composition rather than species number. The two communities have common dominant phylum: Ascomycetes and Basidiomycetes, and common dominant genera: Mortierella and Saitozyma. The functional type was mainly saprotic. Linear discriminant analysis effect size (LEfSe) analysis revealed four biomarker genera (Arthopyrenia, Hypochnicium, Tremella, and Syncephalis) enriched in the A. spinulosa rhizospheric fungal community. Venn diagram analysis identified 169 core genera within this community, with Flavodon exclusively present in the rhizosphere. Mechanistic analysis of community assembly demonstrated that stochastic processes predominantly governed the structuring of rhizospheric fungal communities.DiscussionIn conclusion, this study elucidates the functional composition and assembly mechanisms of rhizospheric fungal communities in A. spinulosa, while identifying keystone fungal taxa potentially critical to its survival. Future investigations should: Quantify the specific contribution of Flavodon to A. spinulosa; Decipher the mechanistic linkages between these fungi and the plant’s stress resistance traits; Implement plant–soil-microbe synergistic restoration strategies to enhance natural regeneration capacity of A. spinulosa populations.